2021
DOI: 10.1155/2021/6634667
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Transcatheter Occlusion of Perimembranous Ventricular Septal Defect with Aortic Valve Prolapse: A Six-Year Follow-Up Study

Abstract: Background. With the rapid development of transcatheter techniques and instruments, transcatheter occlusion for patients with perimembranous ventricular septal defect (pVSD) and aortic valve prolapse (AVP) was constantly being tried, while the efficacy and safety of pVSD with AVP remain controversial. Objective. The aim of this study was to evaluate long-term efficacy and safety of transcatheter occlusion of pVSD with AVP. Methods. We retrospectively analyzed 164 children with pVSD and AVP who underwent transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Aortic valve prolapse (AVP) was graded into three degrees according to the morphology of the right coronary leaflet at the end of diastole during angiography: mild (buckling of the aortic cusp down the left ventricular outflow tract with minimal herniation into the VSD), moderate (prolapse of the cusp and its sinus with obvious herniation into the VSD), and severe (prolapse of the cusp and its sinus through the defect into the right ventricular outflow tract) [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Aortic valve prolapse (AVP) was graded into three degrees according to the morphology of the right coronary leaflet at the end of diastole during angiography: mild (buckling of the aortic cusp down the left ventricular outflow tract with minimal herniation into the VSD), moderate (prolapse of the cusp and its sinus with obvious herniation into the VSD), and severe (prolapse of the cusp and its sinus through the defect into the right ventricular outflow tract) [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Jung et al reported that 86.4% of patients aged <4 years who underwent OVSD closure showed AR progression in only 0.98%, which suggests that early closure of OVSD before aortic valve deformity can prevent the development of aortic valve complications [14]. Zhang et al suggested that once AVP appears, VSD should be closed immediately and the treatment of mild-to-moderate AVP can have a high success rate with fewer complications, which is safe and effective in long-term follow-up [15]. There were no other major complications in this study, right bundle branch block occurred in 12% after transcatheter therapy and 24% after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…At present, transcatheter occlusion for patients with aortic prolapse or intracristal VSD is constantly being tried (15,(17)(18)(19), while the efficacy and safety remain controversial. By reviewing patients with prolapse and intracristal VSD in our cohort, we summarized the following experiences.…”
Section: Discussionmentioning
confidence: 99%